PERAN MEDIA SOSIAL DALAM MENINGKATKAN PENJUALAN PUPUK DI PUSAT KOPERASI UNIT DESA RIAU - Swanda, Fajri; Hudi, Ilham (STKIP Persada Khatulistiwa Sintang, 2024)
Currently, the development of the four-point o (4.0) era is the development of digitalization to create a system that is more efficient, flexible, and connected. The progress of internet usage around the world is increasing rapidly. One of the utilizations of technological advances in sales by using social media. The purpose of this research is through social media PUSKUD Riau can build expand networks with customers and business partners. Thus, it is expected to increase sales. This research uses qualitative methods through interviews and direct observation. The data used in this research is to use primary and secondary data. The location of this research was conducted at the Riau Village Unit Cooperative Center (PUSKUD Riau) on Jalan Jendral Sudirman. Where the object of research was conducted to Mr. Dedi Sahputra as Marketing Manager and Mrs. Mitra Rahayu as marketing. Research results show that social media is a promotional event in providing information to KUD-KUD. Utilization of social media can be an advantage for business people and businesses such as PUSKUD Riau so that they are able to sell their merchandise through online in an unlimited manner with the aim of increasing turnover or profit as well as the limitations of the knowledge of researchers who are still beginners so as to have an impact on the results of research that is less thorough and obtain limited information.